Policy Implementation Model for the Management of Low-Cost Rental Apartments (Rusunawa) in Bandung City - Saepul Rohman; Kamal Alamsyah; Thomas Bustomi (Global Writing Academica Researching & Publishing, 2026)
The main problem of this research centers on the existence of a serious and multidimensional implementation deficit in the management of Low-Cost Rental Apartments (Rusunawa) in Bandung City. This study employs a descriptive research method with a qualitative approach. Data were collected through field observations at strategic locations such as the Cingised, Rancacili, and Sadang Serang Rusunawa complexes, as well as through in-depth interviews with stakeholders from the Housing and Settlement Area Agency (Dinas Perumahan dan Kawasan Permukiman/DPKP) and the Rusunawa Technical Implementation Unit (UPTD) of Bandung City. The findings reveal that the implementation of Rusunawa management policies in Bandung City has not yet been optimal due to weak inter-agency coordination and limited managerial capacity within the implementing organizations. Resource-related factors, particularly the shortage of civil servants and the reactive nature of maintenance budgeting, constitute major obstacles in maintaining the quality of public services. In addition, the study finds that the implementers’ disposition and policy communication variables have not been effective in fostering voluntary compliance among residents, especially in adhering to occupancy duration regulations and administrative requirements. As a solution, this research proposes a policy implementation strengthening model based on service digitalization (Smart Rusunawa) and social engineering to ensure the sustainability of Rusunawa as humane and equitable transitional housing.